Some Observations on the Growth and Survival of the jumbo Prawns Penaeus monodon Fabricius and Penaeus indicus H. M. Edwards in a Solar Salt Works along the Okhamandal Coast of the Gulf of Kutch - P., Gopalakrishnan; V., Krishna Raju; Thaker, Surendra R. (Fishery Technology, 2025)
Early juveniles of the jumbo prawns Penaeus monodon and Penaeus indicus were reared in an earthern pond within a solar salt works to experiment integration of their farming with salt works system along the Gulf of Kutch. During the 180 days rearing in hypersalinity conditions, an average length of 125mm and weight of 22g in the former and an average length of 133mm and weight of l8.5g in the latter were recorded. The survival was only 4.2 and 5.8 % respectively. The growth and survival characteristics related to the hydrology of salt works are analysed and discussed.